ANALISIS CURAH HUJAN RANCANGAN DI KOTA PALEMBANG - Marlina, Ayu (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2018)
Palembang as the capital of South Sumatra Province is one of the metropolitan cities in Indonesia that almost every year the occurrence of floods. Flood disaster is very harmful to the community almost every year. The causes of floods are caused by heavy rainfall. Design rainfall analysis in Palembang City with repeated period is required. Analysis of the rainfall area of 6 rain gauge stations in 2004 - 2015 using thieseen polygon method shows that in 2012 with the highest rainfall of 133 mm. Designed rainfall axis with 2, 5, 10, 25, 50, 100 years return period with 4 methods of Normal Distribution, Log-Normal Distribution, Log-Pearson Type III Distribution, and Gumbel Distribution. From the results of the test method of smyrnov smirnov match obtained the best possible distribution of the rainfall design with the normal method because it has a small error difference of 0.054 compared with other methods. The design rainfall with return periods of 2, 5, 10, 25, 50 and 100 years is 100, 114, 121, 128, 134, and 138 mm. The results of this analysis can be used as a basis for further research on flooding.